Complications of Total Laryngectomy - Bhuiyan, Mohammad Ashequr Rahman; Sarker, Md Zakaria; Haque, Md Nazmul; Khan, Saif Rahman; Mamoon, Towsif Bin; Alam, ABM Khorshed (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To observe Post-operative complications of Total Laryngectomy in advanced Laryngeal Carcinoma Patients. Methods: This prospective observational study was conducted in National Institute of ENT, Tejgaon, Dhaka. Study duration 3 years, from January 2015 to December 2017. 17 patients were selected who underwent total laryngectomy for histologically proven advanced carcinoma larynx. Patients were followed up monthly for 3 months & then after 6 months for life long. Results: The age of the patients ranged from 39 to 66 years. The mean age was 47 years. Most of the cases are supraglottic carcinoma 12 (70.59%), Glottic carcinoma in 5 (29.41%) & no subglottic carcinoma. In this study, out of 12 supraglottic cases, 4 patients were presented in stage III & 8 in stage IV. Among the glottic cases 1 patient presented in stage I, 2 in stage III & 2 patients presented in stage IV. Patients were followed up monthly for 3 months & then after 6 months for life long. 2 patients (11.76%) developed pharyngocutaneous fistula within 7th to 15th post-operative day & these patients were managed conservatively which involved adequate drainage, frequent dressing & fresh blood transfusion. With these conservative management fistula healed completely within 3 to 4 weeks. 3 patients (17.65%) developed wound infection. Wound swab was sent for culture & sensitivity and antibiotics changed accordingly. Wound healed within 2-3 weeks with conservative treatment & adequate aseptic dressing. 1 patient (5.88%) developed postoperative hematoma which was drained immediately. This patient developed wound infection later on & was managed conservatively. 2 patients (11.76%) developed stomal recurrence 4 months after surgery, which was confirmed by biopsy. The cases were inoperable & were sent for radiotherapy. 2 patients (11.76%) developed dysphagia due to pharyngeal stenosis 4 months after surgery. Conclusion: The most frequent troublesome immediate complication is pharyngocutaneous fistula all of which have been treated conservatively with satisfactory result. Preoperative radiotherapy is an important risk factor for the development of pharyngocutaneous fistula in total laryngectomy. Bangladesh J Otorhinolaryngol; April 2019; 25(1): 10-18